Risk Factors for Chemotherapy-Induced Peripheral Neuropathy Caused by Nanoparticle Albumin-Bound Paclitaxel in Advanced Breast Cancer. (13th September 2022) - Guo, Qie; Zhang, Haonan; Li, Xiao; Quan, Xianghua
Abstract : Breast cancer (BC) is one of the most common malignancies affecting women and the leading cause of related mortality worldwide. An estimated 2260000 new cases of BC were diagnosed in 2020, which have seriously threatened the health. Paclitaxel (PTX), a natural product isolated from the bark of the pacific yew, has been found to be effective in treating advanced BC. Chemotherapy-induced peripheral neuropathy (CIPN), which refers to the damage to the peripheral nerves caused by exposure to a neurotoxic chemotherapeutic agent, is a common side effect affecting the patients undergoing PTX chemotherapy. Significant research efforts are needed to identify the various risk factors associated with CIPN. Here, a univariate analysis in BC patients with nanonab-PTX treatment was performed. The rate of CIPN in BC patients with albumin-bound paclitaxel (nab-PTX) for more than four weeks was significantly higher than that of patients with chemotherapy for less than four weeks. Moreover, the rate of CIPN in BC patients receiving nab-PTX first-line chemotherapy was remarkably higher than that in BC patients receiving paclitaxel as a sequence scheme. Taken together, chemotherapy cycles and the priority of nab-PTX-based chemotherapy can be considered the potential risk factors for CIPN induced by nab-PTX.